Ketidaktepatan Kode Sebab Dasar Kematian menjadi Penyebab Kerugian 600 Juta Dana di Unit ICCU RSUD dr Moh Saleh Probolinggo - Novita sari; Dewi Rokhmah; Isa Ma’rufi (Multidisciplinary Journal, 2020)
The coding of the diagnosis is important for patient care, hospital management and research. However, coding accuracy is a major problem in the diagnosis process and has impact on hospital income levels. This study is about the inaccuracy of the underlying cause of death coding toward the level of hospital income. The Methods employed is the Analysis of the accuracy of the diagnosis according to the mortality coding rules compiled in the Instruction Coding Manual of the World Health Organization (WHO). Afterwards, the percentage of losses is calculated using the system of INAcbg’s, in the Diagnosis Based on Indonesian Case system. The result shows that, out of 176 files were studied, 114 files or 65% of the diagnosis codes of the cause of death were incorrect, 57 files or 32% were correct and 5 files or 3% of files were not coded. Further, the study found out that 65% of these inaccuracies contributed to hospital losses which includes 40-75 % loss with the total loss received by the hospital as much as IDR 597,849,006 or nearly 600 million rupiah. The research concludes that the absence of a diagnosis of death increases hospital losses by more than 40% to 75%. Keywords: Accuracy, Code of Basic Cause of Death, ICD 10